2018
DOI: 10.11648/j.ajbes.20180401.13
|View full text |Cite
|
Sign up to set email alerts
|

Bread Wheat Varietal Development and Release in Southeastern Highlands of Ethiopia

Abstract: Four improved bread wheat varieties; Mandoyu (WORRAKATTA/PASTOR), Sanate (14F/HAR1685), Obora (UTIQUE96/FLAG-1) and Dambel (AGUILAL/3/PYN/BAU//MILAN) are developed from ICARDA materials and released in 2014 and 2015, respectively for highland and mid altitude areas of Bale and similar agro-ecologies. The new varieties were tested along with three standard checks (Madawalabu, Sofumer and Tusie) and one local check (Hollandi) at three environments in 2011 to 2012 and 2012 to 2013, respectively during main croppi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…e average productivity of wheat at the national level, South Nation, Nationalities, and People Regional State (SNNPRS), and Wolaita zone of SNNPRS is 2.67, 2.58, and 1.45 ton•ha −1 , respectively [2]. However, potential yield of wheat goes beyond 5 t•ha −1 that rises questionable yield gap between farmers' and attainable yield of the crop [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…e average productivity of wheat at the national level, South Nation, Nationalities, and People Regional State (SNNPRS), and Wolaita zone of SNNPRS is 2.67, 2.58, and 1.45 ton•ha −1 , respectively [2]. However, potential yield of wheat goes beyond 5 t•ha −1 that rises questionable yield gap between farmers' and attainable yield of the crop [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, about 76% and 10% of the farmers grew modern bread wheat varieties and obsolete varieties, respectively. Several studies also indicated widespread seed recycling practices [25,26,19,27].…”
Section: Yield and Economic Effects Of Seed Recyclingmentioning
confidence: 99%
“…Nonetheless, during the FGD, farmers opined that a one-time or twice recycling did not cause noticeable yield reduction. Yet, [25,14] reported that fresh certified seeds increase productivity and farmer's efficiency in comparison to frequently recycled seeds. The productivity and efficiency gains indicate that promoting fresh certified wheat seeds has the potential to raise production using the available improved seed technologies at the most efficiency.…”
Section: Yield and Economic Effects Of Seed Recyclingmentioning
confidence: 99%
“…In Ethiopia, about 76% and 10% of the farmers grew modern bread wheat varieties and obsolete varieties, respectively. Several studies also indicated widespread seed recycling practices [19,[25][26][27].…”
Section: Yield and Economic Effects Of Seed Recyclingmentioning
confidence: 99%
“…Nonetheless, during the FGD, farmers opined that a one-time or twice recycling did not cause noticeable yield reduction. Yet, [14,25] reported that fresh certified seeds increase productivity and farmer's efficiency in comparison to frequently recycled seeds. The productivity and efficiency gains indicate that promoting fresh certified wheat seeds has the potential to raise production using the available improved seed technologies at the most efficiency.…”
Section: Yield and Economic Effects Of Seed Recyclingmentioning
confidence: 99%